2021
DOI: 10.3390/plants10051010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Semi-Automated Bioreactors for In Vitro Propagation of Taro (Colocasia esculenta L. Schott)

Abstract: Taro is important for its nutritional content, medicinal use, and bioethanol production. The aim of the present study was to compare different semi-automated bioreactors (SABs) during in vitro multiplication of C. esculenta. The SABs used were temporary immersion bioreactors (TIBs), SETIS™ bioreactors and ebb-and-flow bioreactors; semi-solid culture medium was used as a control treatment. At 30 d of culture, different developmental variables, determination of chlorophyll, stomatal content, and survival percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…From the results of the present study, a similar positive effect on light acquisition with the use of the ElecTIS bioreactor can be hypothesized. In accordance, the minor chlorophyll and carotenoid amounts from shoots cultured in glass jars with gelled media, observed also in blackberry, was reported by Mancilla-Álvarez et al [24], who hypothesized that the culture in climatic chambers with classic glass jars, positioned vertically on multiple levels, limits the amount of light the explants receive. However, a medium effect (liquid or gelled) on these parameters cannot be excluded.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…From the results of the present study, a similar positive effect on light acquisition with the use of the ElecTIS bioreactor can be hypothesized. In accordance, the minor chlorophyll and carotenoid amounts from shoots cultured in glass jars with gelled media, observed also in blackberry, was reported by Mancilla-Álvarez et al [24], who hypothesized that the culture in climatic chambers with classic glass jars, positioned vertically on multiple levels, limits the amount of light the explants receive. However, a medium effect (liquid or gelled) on these parameters cannot be excluded.…”
Section: Discussionsupporting
confidence: 82%
“…The results in this study demonstrate the efficiency of the ElecTIS bioreactor in promoting the shoot growth and proliferation of blackberry shoots coming from SGS at a low temperature (4 • C) and in darkness, in comparison with the gelled medium. In recent years, the mass production of micropropagated plants, based on the use of liquid culture in TIS bioreactors, has been established and developed for a wide range of species, e.g., banana [22], myrabolan rootstock [23], taro [24,25] and stevia [26]. Mancilla-Álvarez et al [27] suggested that the assimilation of sugars, nutrients and growth regulators from the liquid culture medium when in contact with the entire surface of the explant could be an explanation for the increase in the multiplication rate of Colocasia esculenta, while the lower availability of organic and inorganic compounds in the gelled medium, due to the limited contact of shoots at their base, determines the lower multiplication rates.…”
Section: Discussionmentioning
confidence: 99%
“…The control group was significantly higher than all other treatments. Irradiance is an important factor in physiological processes that affects the synthesis of chlorophyll [26], leading to potentially two main reasons for our results:…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al [44] revealed that biomass production from Anoectochilus formosanus was less efficient when culturing was performed under temporary immersion. In a recent study on in vitro multiplication of Colocasia esculenta, applying different culture systems demonstrated that the highest regeneration rate was with TIS [57].…”
Section: Culture System and Biomass Productionmentioning
confidence: 99%